Determinants of Successful Crew Recruitment in Shipping Companies - Neng Sri Komala Komala; Muhammad Thamrin; Prasadja Ricardianto; Endri Endri; Edi Abdurahman (Goodwood Publishing, 2026)
Purpose: This study aims to examine and analyze the effects of training, work experience, education, and personal characteristics on ship crew recruitment success in Indonesian shipping companies, with competence and work experience as mediating and moderating variables, respectively. Methodology: A quantitative explanatory research design was employed. The population consisted of HR division employees at various levels in shipping companies in Indonesia. The sample size was determined using the Slovin formula and selected through proportional random sampling method. Data were collected using structured questionnaires with a five-point Likert scale and were supported by focus group discussions (FGDs). SEM-PLS was used for the data analysis. Results: Training, education, and personal characteristics positively and significantly affected the competence and recruitment success. Competence also positively influenced recruitment success and mediated the effects of training, education, and personal characteristics on recruitment success. Additionally, work experience strengthens the relationship between competence and recruitment success, confirming its moderating role. Conclusions: This study highlights the importance of competence in improving recruitment outcomes in maritime HR practices. It also emphasizes that training, education, and personal characteristics enhance competence, which, in turn, affects recruitment success. Work experience plays a key role in strengthening this relationship. Limitations: The study is limited to HR personnel in Indonesian shipping companies, with a small sample size, affecting generalizability. External factors, such as maritime regulations and digital recruitment technologies, were not considered. Contributions: This study contributes to maritime HR management by developing a model of crew recruitment success, incorporating competence and work experience, and providing a comprehensive understanding of recruitment effectiveness in shipping companies.